Conceptual framework for integrating environmental sustainability into supplier selection in procurement decisions - Joshua Ayarkwa; Tonny Ograh; Dickson Oseiâ€Asibey; Alex Acheampong; Peter Amoah (Sustinere: Journal of Environment and Sustainability, 2021)
Theories are used to improve conceptualization of research ideas. These theories enhance valuable elucidations that helps us to grasp the meaning of research findings. Nevertheless, the use of theories to promote studies in green supplier selection in procurement decisions has attracted little attention. With the emergence of sustainable procurement, public procurement practitioners in Ghana are yet to achieve relevant knowledge on green supplier selections due to insufficient knowledge and inadequate appropriate frameworks. The flagrancy of the consequences of public procurersâ€™ failure to integrate environmental considerations into supplier selection explains the adoption of a multi-theory approach for comprehension of the dynamics of green integration into supplier selection. In this paper, the practicality of three theories for improving the understanding of the influential factors enhancing the integration of environmental sustainability into supplier selection was reviewed. The three theories are: Resource Based Theory, Human Capital Theory and Absorptive Capacity Theory. This review uncovered knowledge management, top management commitment, and environmental management capabilities as important elements needed for the integration of environmental sustainability into supplier selection in public procurement. The theoretical review yielded a framework that conceptualizes knowledge and capabilities of practitioners relevant to incorporation of environmental sustainability into supplier selection in public procurement.